A comparative study of motor skills of physiotherapy and pharmacy students at Medical University of Lublin and their opinions concerning the role of physical activity in their future professional careers - Chmiel, Justyna; Chołuj, Kamil; Fijewski, Adam; Majcher, Piotr (Polish Journal of Public Health, 2009)
Introduction. From the human motoricity point of view, motor skills are sets of predispositions connected by a common, dominant biological and motor background that are shaped by genes and environment. These, via the process of mutual interaction, when combined with motor abilities offer potential for motoricity. Aim. The aim of the work is a comparison of the test results concerning specific motor skills. Tests were conducted on a group of 1st year physiotherapy and pharmacy students of Medical University of Lublin. Material and method. The research covered 2 groups: physiotherapy and pharmacy students of Medical University of Lublin; each group included 27 members. The survey was based on Stefan Pilicz motor skills test and Ludwik Denisiuk endurance test. The survey was supplemented with the data collected from the questionnaire. Results. General level of physical fitness for physiotherapy students assessed on the basis of Pilicz test reached 246 points, which is 64 points higher than the one for pharmacy students. All of physiotherapy students stated that apart from obligatory PE classes they do some extra physical exercises. When it comes to pharmacy students, only 59% admit to do some additional exercises, and only 41% of them attend the obligatory PE classes once in a week. Discussion. A higher level of physical fitness of the physiotherapy students stems among other things from the fact that physical fitness tests are conducted during enrollment. Apart from that, the course of the studies and the character of future job in itself make it necessary to sustain a high level of fitness. Conclusion. Physiotherapy students represent a higher level of physical fitness than pharmacy students. Contrary to the pharmacy students, physiotherapy students see a strong correlation between the level of physical fitness and one’s profession.